Experimental characterization of an ultra-broadband dual-mode symmetric Y–junction based on metamaterial waveguides. (January 2023) - Fernández de Cabo, Raquel; Vilas, Jaime; Cheben, Pavel; V. Velasco, Aitor; González-Andrade, David
Highlights: Detailed experimental study that demonstrates the broadband performance and relaxed fabrication tolerances of an SWG-based Y–junction. Fundamental transverse-electric (TE0 ) mode excess loss per splitter measured through linear regression of the response of cascaded SWG and conventional Y–junctions. Excess losses for the first-order transverse-electric (TE1 ) mode measured using a mode multiplexer, potentially enabling new applications of the proposed device. Excess losses below 0.3 dB for TE0 within 260 nm (1420–1680 nm) and below 1 dB within a 100 nm bandwidth (1475–1575 nm) for TE1 . Abstract: Silicon photonic integrated circuits routinely require 3-dB optical power dividers with minimal losses, small footprints, ultra-wide bandwidths, and relaxed manufacturing tolerances to distribute light across the chip and as a key building block to form more complex devices. Symmetric Y–junctions stand out among other power splitting devices owing to their wavelength-independent response and a straightforward design. Yet, the limited resolution of current fabrication methods results in a minimum feature size (MFS) at the tip between the two Y–junction arms that leads to significant losses for the fundamental mode. Here we propose to circumvent this limitation by leveraging subwavelength metamaterials in a new type of ultra-broadband and fabrication-tolerant Y–junction. An exhaustive experimental study over a 260 nm bandwidth (1420 nm – 1680 nm) shows excess loss below 0.3 dB for the fundamental transverse-electric mode (TE0 ) for a high-resolution lithographic process (MFS ∼ 50 nm) and < 0.5 dB for a fabrication resolution of 100 nm. Subwavelength Y–junctions with deterministically induced errors of ± 10 nm further demonstrated robust fabrication tolerances. Moreover, the splitter exhibits excess loss lower than 1 dB for the first-order transverse-electric mode (TE1 ) within a 100 nm bandwidth (1475 nm – 1575 nm), using high-resolution lithography.